Low-Intensity Photobiomodulation Decreases Neuropathic Pain in Paw Ischemia-Reperfusion and Spared Nervus Ischiadicus Injury Experimental Models - Pigatto, Glauce R.; Quinteiro, Maiara H.S.; Nunes-de-Souza, Ricardo L. [UNESP]; Coimbra, Norberto C.; Parizotto, Nivaldo A. (Wiley, 2020)
Background: There is a wide range of animal models available today for studying chronic pain associated with a variety of etiologies and an extensive list of clinical manifestations of peripheral neuropathies. Photobiomodulation is a new tool for the treatment of pain in a convenient, noninvasive way. Objective: The aim of this work is to elucidate the effects of infrared light-emitting diodes (LEDs) on behavioral responses to nociceptive stimuli in chronic pain models. Methods: Forty-eight Swiss male mice weighing 25 to 35 g were used. Two chronic pain models, ischemia-reperfusion (IR) and spared spinal nerve injury, were performed and then treated with infrared LED irradiation (390 mW, 890 nm, 17.3 mW/cm2, 20.8 J/cm2, for 20 minutes). The behavioral tests used were a mechanical hypersensitivity test von Frey test) and a cold allodynia test (acetone test). Results: The results showed that, in the IR model, the infrared LED had a significant effect on mechanical stimulation and cold allodynia on every day of treatment. In the spared nerve injury model, an analgesic effect was observed on every treatment day (when started on the 3rd and 7th days after the surgery). In both models, the effect was abolished when the treatment was interrupted. Conclusions: These findings suggest that photobiomodulation therapy may be a useful adjunct treatment for chronic pain.
Keywords: allodynia; antinociceptive effect; chronic pain; light-emitting diode; photobiomodulation